Pengaturan Perpajakan Daerah Dalam Sistem Hukum Pajak Indonesia - mustqiem mustaqiem (Jurnal Hukum IUS QUIA IUSTUM, 2006)
Based on Statutes and regulatiuon above, the enacttment of local taxation weredecen tralization pattern, even though boththe systems are use the same time. The local regulation have function as legalbase forimposition the localtax, to fulfill the formal and materiil standart that have been determined by laww and regulation upon him.